PENENTUAN KONSENTRASI SODIUM DODECYL SULFATE DALAM PENGENCER RINGER LAKTAT-KUNING TELUR UNTUK PRESERVASI SEMEN AYAM PELUNG (Determination of Sodium Dodecyl Sulfate Concentration in Ringer Lactate-Egg Yolk Extender for Pelung Rooster Semen Preservation) - Nu’man Hidayat; Cece Sumantri; Rudi Afnan (Jurnal Kedokteran Hewan, 2016)
The objective of this experiment was to determine the addition of sodium dodecyl sulfate (SDS) to Ringer Lactate-Egg Yolk (RL-EY) extender on pelung chicken semen preservation. Semen was collected three times a week from three pelung chickens. Collected semen was evaluated macroscopically and microscopically. Only ejaculates of at least 70% sperm motility was then divided into three equal microtubes. Each of them diluted with RL-EY with ratio 90%:10%, then added with 0.00, 0.025, and 0.05% SDS respectively. The liquid semen then stored at 5 °C for 72 hours. Sperm motility and viability were observed every 12 hours. The addition of 0.025% SDS showed higher spermatozoa motility and viability (72.08±1.44% and 80.82±1.30%) which were significantly higher (P0.05) than 0.00 and 0.05% SDS addition at 24 hours of storage. There was no differences on the spermatozoa motility and viability between 0.00 and 0.05% SDS addition. The decrease of spermatozoa motility and viability was observed in 0.025% SDS addition (4.17±0.56% and 4.65±0.59%, respectively) that significantly lower compared to 0% and 0.05% SDS addition at 24 hours of storage. In conclusion, 0.025% SDS addition in a Ringer Lactate -Egg Yolk extender maintained pelung spermatozoa motility and viability better than 0.00 and 5% SDS addition.